2021
DOI: 10.1017/s1355617721000655
|View full text |Cite
|
Sign up to set email alerts
|

Two Immersive Virtual Reality Tasks for the Assessment of Spatial Orientation in Older Adults with and Without Cognitive Impairment: Concurrent Validity, Group Comparison, and Accuracy Results

Abstract: Objective: Spatial disorientation is common in Alzheimer’s disease (AD), Mild Cognitive Impairment (MCI), and preclinical individuals with AD biomarkers. However, traditional neuropsychological tests lack ecological validity for the assessment of spatial orientation and to date, there is still no gold standard. The current study aimed to determine the validity and accuracy of two virtual reality tasks for the assessment of spatial orientation. Methods: We adapted two spatial orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 91 publications
1
19
0
Order By: Relevance
“…In addition, participants reported high levels of immersion and presence; such finding is considered essential for the cognitive engagement capacity and for the test to be considered ecological. 17 Our results are in line with a study by Ijaz et al, 24 which evaluated the applicability and usability of an immersive VR platform to assess spatial navigation in older adults. Their results revealed that, despite the relative novelty of VR technology for this population, they made few navigation errors, identified challenging landmarks successfully and presented high levels of presence.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, participants reported high levels of immersion and presence; such finding is considered essential for the cognitive engagement capacity and for the test to be considered ecological. 17 Our results are in line with a study by Ijaz et al, 24 which evaluated the applicability and usability of an immersive VR platform to assess spatial navigation in older adults. Their results revealed that, despite the relative novelty of VR technology for this population, they made few navigation errors, identified challenging landmarks successfully and presented high levels of presence.…”
Section: Discussionsupporting
confidence: 91%
“…TO presents a greater difference between subjects with MCI or dementia and those without impairment [ 66 ]. Other studies, however, have observed that deterioration of SO in MCI is associated with a higher risk of progression to AD [ 67 ] and spatial disorientation is common in AD [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The median VR study had 48 participants (range = 42–60) with a median age of 71.66 years (range of sample averages = 71.13–72.35). Race was reported for two studies, with one study reporting 100% Asian participants (Chua et al, 2019) and the other reporting 75% Hispanic White, 18.75% Hispanic Japanese, and 6.25% Hispanic Black participants (da Costa et al, 2022). One study required participants to speak Portuguese (da Costa et al, 2022), while the remaining two studies did not report a language requirement.…”
Section: Novel Technological Assessments Versus Traditional Measures ...mentioning
confidence: 99%